Pengaruh Struktur Modal Terhadap Manajemen Laba - Eka Eka; Goso Goso; Muh. Halim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of the study was to analyze and determine the impact of capital structure as measured by the debt-to-asset ratio (DER) and the debt-to-asset ratio (DAR). financial ratios on earnings management calculated using the Jones and Modified Jones discretionary accruals models. The secondary data used is the financial statements of PT. Piranti Jagad Raya for the 2018-2022 period. The data analysis technique uses simple linear regression with the help of SPSS Statistics 25. The results and findings of the study show that capital structure has a significant positive effect on earnings management. This indicates that the higher the equity of a company, the more efficient use of earnings management. Implications for PT. The Jagad Raya tool is to avoid agency problems and information asymmetry between agents and principals. Companies can implement more efficient earnings management or suppress the use of earnings management to avoid opportunistic actions so that companies have healthy financial reports. Keywords: Earnings Management, Capital Structure, Agency teori